WAYS TO INCREASE COMPETITIVENESS OF PRODUCTS OF LIGHT INDUSTRY ENTERPRISES UNDER CONDITIONS OF MODERNIZATION OF ECONOMY - Ibragimova, K. S.; Ishmuhamedova, M. X.; Isaeva, L. A. . (International Journal of Psychosocial Rehabilitation, 2020)
Research paper portrays premise of the analysis of the nourishment business market and light industry showcase over the span of modernization the progressions that happen in their structure, rivalry and serious condition are distinguished and advocated. The analysis of the components, permitting territorial makers to make upper hand on the business sectors of the modernized ventures is satisfied. The chance of some better utilization of assets, especially work and immaterial resources associated with human capital and made by imaginative work, improving aptitudes, growing ability is demonstrated.